Antimicrobial activity of tetraacetylethylenediamine-sodium perborate versus sodium hypochlorite against Enterococcus faecalis - Sahar Shakouie; Amin Salem Milani; Mahsa Eskandarnejad; Saeed Rahimi; Mohammad Froughreyhani; Saeede Galedar; Ehsan Ranjbar (Tabriz University of Medical Sciences, 2016)
Background. This study evaluated the antimicrobial activity of Tetraacetylethylenediamine-sodium perborate (TAED-SP) in comparison to 2.5% and 5% sodium hypochlorite (NaOCl) against Enterococcus faecalis. Methods. A standard suspension of E. faecalis was inoculated on 60 plates containing Mueller-Hinton agar culture medium. Four sterile disks of Beckman filtration paper were placed on each plate. TAED-SP, 5% and 2.5% NaOCl were placed on three disks. Sterile physiologic saline was placed on the fourth disk as negative control. After 24-hour incubation, the diameter of the inhibition zone around the disks was measured using a transparent ruler. One-way Analysis of Variance (ANOVA) was used to compare the mean zone of microbial growth in the groups. P-values less than 0.05 were considered statistically significant. Results. There was a significant difference in the diameter of the inhibition zones between groups (P < 0.05). The Tukey post hoc test showed a higher diameter of the inhibitory zone with TAED-SP than that of 2.5% NaOCl. However, there were no significant differences between the inhibitory zones of TAED-SP and 5% NaOCl. Conclusion. TAED-SP and 5% NaOCl have similar antibacterial activity against E. faecalis; however, TAED-SP has a greater antibacterial effect compared to 2.5% NaOCl.